Levantamiento de suelos del Municipio de Tuxpan Nayarit, México - José I. Bojorquez Serrano; José López García (Investigaciones Geográficas, 1997)
This paper presents the lesults of a semidetailed soil survey using the methodology proposed by Elbersen et al. (1974), updated by Villota and Forero (1986) and the Soil Survey Staff (1993); through physiographic and photointerpretation analysis soil map units were delineated, these were supported with the traditional knowledge of peasants, soils description was based on the manual Cuanalo (1990) 35 profiles were described and a total of 140 samples were physicaly and chemicaly analysed to classify their taxonomy. The availability of nutrients was determined and general practices of management for each unit of soil map units are suggested.